Effects of Early Warning Score (EWS) Tutorial Simulation on Nurses' Knowledge and Clinical Performance - Damayanti, Roshy; Trisyani, Yanny; Nuraeni, Aan (Nurse Media Journal of Nursing, 2019)
Background: The Early Warning Score (EWS) system has been recommended for early identification tool of deterioration. However, its implementation has not been optimal; one of which is due to the low level of knowledge and understanding of EWS among nurses.Purpose: This study aimed to determine the effects of EWS tutorial simulation on nurses’ knowledge and clinical performance.Methods: This study employed a pretest posttest quasi-experimental design with a control group. Purposive sampling was used to recruit the samples of 42 respondents each in the intervention group and control group. The data were collected using the questionnaires to measure the knowledge and clinical performance, and analyzed using Chi square, Wilcoxon and Mann-Whitney tests.Results: The results showed that there were differences in the pre-test and post-test of knowledge and clinical performance in the intervention group and control group (p<0.001). There was also a significant difference in clinical performance between the intervention group and the control group (p<0.001). However, no significant difference in knowledge was found between.Conclusions: Tutorial simulation of EWS had an effect on increasing nurses’ clinical performance. Although there was no significant difference in knowledge between the intervention group and the control group, but the intervention group showed a better value than the control group. EWS tutorial simulation can be used as one of the training methods to increase nurses' knowledge and clinical performance in EWS.